Relation of health behaviors to gardening among the Prairie Band Potawatomi Nation in Kansas - Randall, Chandalar (Kansas State University, 2016)
Low fruit and vegetable (FV) intake and low physical activity (PA) levels are linked to increased risk of chronic diseases such as overweight and obesity, diabetes mellitus, and cardiovascular diseases. American Indians/Alaska Natives (NA) seem to be even more susceptible to these chronic diseases when compared to the general United States (U.S.) population, though little research has been conducted on smaller NA tribes. Gardening has been shown to increase vegetable consumption and be a means of PA. The purpose of this study was to see if gardeners of the Prairie Band Potawatomi Tribe (PBPN) in Kansas were more likely to have positive health indicators than non-gardeners. The objective was to discover if PBPN gardeners were more likely than non-gardeners to eat the daily recommended amount of fruit (2 servings) (Center for Nutrition Policy and Promotion, 2015a), eat the daily recommended amount of vegetables (3 servings) (Center for Nutrition Policy and Promotion, 2015b), meet the weekly recommended amount of PA (Centers for Disease Control and Prevention, 2009), perceive their health to be good, and determine if PBPN gardeners meet the weekly recommended amount of PA through gardening activities. Surveys were utilized to gather gardening and health information for PBPN tribal members. Data was coded and descriptive and contingent statistical analyses were performed. Gardeners were more likely than non-gardeners to eat the daily recommended amount of vegetables, the daily amount of both FV, and meet all FV and PA recommendations. Most gardeners met PA recommendations through gardening activities. Gardeners were not more likely than non-gardeners to eat the daily recommended amount of fruit, meet the recommended amount of PA, or to perceive their health as good. Encouraging gardening seems promising as a means of encouraging healthy lifestyles.
Keywords: Native American; Gardening; Fruits and vegetables; Physical activity; Health